Quality of care among patients diagnosed with atrial fibrillation in Greenland - Marie Tolver Nielsen; Maja Hykkelbjerg Nielsen; Stig Andersen; Sam Riahi; Uka Wilhjelm Geisler; Michael Lynge Pedersen; Nadja Albertsen (International Journal of Circumpolar Health, 2024)
This cross-sectional study sought to assess the prevalence of atrial fibrillation (AF) diagnosis in Greenland among various age groups and examine the corresponding quality of care. We collected data from Greenland’s electronic medical records and evaluated the quality of care using six internationally recommended indicators, which are: percentage of AF patients with an assessment of smoking status within the previous year, an assessment of body mass index within the previous year, assessment of blood pressure within the previous year, measurement of thyroid stimulating hormone (TSH), treatment with an anticoagulant and percentage of patients with a measurement of serum-creatinine. We found the prevalence of AF among patients aged 20 years or older in Greenland to be 1.75% (95% CI 1.62–1.88). We found an increasing prevalence of AF with age and a greater proportion of men than women until the age of 74 years. Our study suggests that the associated quality of care could be higher as the requirement of only one of the six quality indicators was met. A lack of registration may partly explain this, and initiatives to improve the quality of care are recommended.